Fundamental Environment dan Kinerja Keuangan (Studi pada Perusahaan Pertambangan Dan Manufaktur Yang Terdaftar di ISSI 2016-2019) - Asaqdah, Siti Halizah; Putra, Rosyid Nur Anggara (AKTSAR: Jurnal Akuntansi Syariah, 2021)
The study aims to examine the impact of environmental performance, environmental disclosure and ISO 14001 on financial performance. The independent variables used to consist of environmental performance as measured by the PROPER rating, environmental disclosure as proxied by the Indonesia Environmental Reporting (IER) index, and ISO 14001 measured by a dummy variable, while financial performance as proxied by ROA is the dependent variable. The purposive sampling technique was used for sampling which resulted in a total of 30 sample companies which were mining and manufacturing companies that were included in the Indonesian Sharia Stock Index (ISSI) from 2016 to 2019. Multiple linear regression tests were used in the data analysis technique. The test results show that ISO 14001 has a positive and significant effect on financial performance, while environmental performance and environmental disclosure have no effect on financial performance.